Growing european market and the implications of 1991 for the Caribbean: what are we doing and what do we need to do? - Lestrade, Swinburne ([The author] [Port of Spain]TT, 1991)
Sees the immediate challenge for 1992 as finding ways of minimising the potential damage to the economic and social systems of our countries, deriving from the likely fall-off in exports of the critically important traditional sectors of the economies. Sees the longer range challenge as taking advantage of the opportunities afforded by the expanded EC market, and placing ourselves in a position to trade beneficially in that market. Considers the regional private sector as playing a pivotal role in seeing the Caribbean through to the 21st century and identifies 7 ways in which this can be achieved.